KRYGSHELDE / WAR HEROES: LT.KDR. D.A. HALL, DIE GROOTHARTIGE SKIPPER - Kroukamp, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
This article recalls the part lieutenant-commander D.A. "Stoker" Hall, one of the South African naval heroes of World War II, and his last command, the fregate Natal, has played in the Battle of the Atlantic. Natal was one of the two South African warships that sank enemy submarines - and Lt Cmdr Hall was the only South African Naval Commander to destroy a German U-boat.